Does coronavirus disease 2019 kill more elderly men than women due to different hormonal milieu - Apurva Tandon; Vishal R Tandon; Sudhaa Sharma; Annil Mahajan (Wolters Kluwer Medknow Publications, 2022)
Preliminary data depicts a much greater prevalence and high case-fatality rate in advanced age males as compared to age-matched women with severe acute respiratory syndrome-coronavirus-2 infections with high morbidity, mortality, high referral, and admission to intensive care unit with severe sequelae. However, the literature search revealed both for and against studies in this context. Thus, at present, in light of the mixed studies, it cannot be established whether low testosterone levels in aging hypogonadal males create a permissive environment for severe response to coronavirus disease 2019 (COVID-19) infection and can it increase the morbidity or mortality, or on the contrary if the virus inhibits androgen formation. Hence, it is highly warranted to establish the said hypothesis by conducting large statistically powered clinical studies in future. Further, it is highly indicated that impact of sex hormones and gender on the incidence and case fatality of the disease and hormones as a treatment according to sex and gender for COVID requires further scientific research by the research community before it is actually recommended to mitigate the COVID-19 disease course among elderly men and women at large.